1998
DOI: 10.1055/s-2007-1010236
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Factor XIII on Bleeding in Coronary Surgery

Abstract: Factor XIII influences bleeding after coronary surgery and can reduce the need for blood transfusions. In patients with prolonged diffuse bleeding, we therefore recommend substitution of Factor XIII.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 0 publications
2
49
0
5
Order By: Relevance
“…Acquired factor XIII deficiency is common following cardiopulmonary bypass (147)(148)(149)(150) and children may be particularly susceptible to the deficiency. In children undergoing open heart surgery for congenital cardiac defects, those with low factor XIII levels have a higher risk for developing myocardial edema requiring delayed sternal closure (151).…”
Section: Role Of Transglutaminases In Vascular Permeabilitymentioning
confidence: 99%
“…Acquired factor XIII deficiency is common following cardiopulmonary bypass (147)(148)(149)(150) and children may be particularly susceptible to the deficiency. In children undergoing open heart surgery for congenital cardiac defects, those with low factor XIII levels have a higher risk for developing myocardial edema requiring delayed sternal closure (151).…”
Section: Role Of Transglutaminases In Vascular Permeabilitymentioning
confidence: 99%
“…Moreover, the FDA approval of Fibrogammin/Corifact for routine prophylaxis and perioperative bleeding management in congenital FXIII deficiency was based on the confirmed efficacy and safety profile established in 12 clinical trials with a total of 187 patients receiving 3,930 doses [12]. Fibrogammin/Corifact has also been shown to be efficacious in cases of acquired FXIII deficiency, such as reducing bleeding in ulcerative colitis [13], minimizing the incidence of myocardial edema during cardiac surgery in newborns and young children with congenital heart disease [14], reducing bleeding and transfusion requirements, and improving clot firmness during surgery [15,16,17], and reducing bleeding and red blood cell (RBC) transfusion requirements following stem cell transplantation [18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…[1] (Havel et al, 1991); [2] (Shainoff et al, 1994); [3] (Chandler et al, 2001); [4] (Chandler and Velan 2003); [5] (Godje et al, 1998); [6] (Boisclair et al, 1993); [7] (Teufelsbauer et al, 1992); [8] (Hunt et al, 1998). were observed (Table 4) and attributed to blood loss, hemodilution and activation, the latter of which was demonstrated by elevated PF4 and β-TG concentrations during the ECC period (Table 3). Evidence of coagulation system activation was demonstrated by a doubling of TAT complex during the ECC period, despite hemodilution and adequate heparinization of study animals as demonstrated by suitably prolonged ACT values of >400 s. D-dimer concentrations appeared to be relatively insensitive to ECC, despite evidence of coagulation activation, and no remarkable changes were observed during the post-ECC period (Table 3).…”
Section: Clinical and Anatomic Pathology Of Ecc Study Animalsmentioning
confidence: 99%